Towards Understanding Programs Through Wear-Based Filtering - DeLIne, Robert; Khella, Amir; Czerwinski, Mary; Robertson, George (SoftVis '05 Proceedings of the 2005 ACM symposium on Software visualization, 2005)
Large software projects often require a programmer to make changes to unfamiliar source code. This paper presents the results of a formative observational study of seven professional programmers who use a conventional development environment to update an unfamiliar implementation of a commonly known video game. We describe several usability problems they experience, including keeping oriented in the program’s source text, maintaining the number and layout of open text documents and relying heavily on textual search for navigation. To reduce the cost of transferring knowledge about the program among developers, we propose the idea of wear-based filtering, a combination of computational wear and social filtering. The development environment collects interaction information, as with computational wear, and uses that information to direct the attention of subsequent users, as with social filtering. We present sketches of new visualizations that use wear-based filtering and demonstrate the feasibility of our approach with data drawn from our study.